The complete mitochondrial genomes of three populations in Luehdorfia chinensis (Leech, 1893) (Lepidoptera: Papilionidae), with a phylogenetic analysis of Papilionidae. (3rd July 2019) - Chen, Tao; Chen, Xiaoning; Wang, Jia; Wu, Sijia; Zhang, Huanhuan; Xing, Lianxi; You, Ping
Abstract: Luehdorfia chinensis (Leech, 1893) is an endemic and protected butterfly in China; thus, sequencing the mitochondrial genome (mitogenome) of this species is of significance. We determined the mitochondrial genomes of three populations (Huayin, Zhouzhi and Ningshan) of L. chinensis, performed a comparative analysis of these genomes and previously sequenced mitogenomes of the genus Luehdorfia, and reconstructed the phylogeny of Papilionidae to clarify whether the Ningshan population of L. chinensis represents a separate species. The mitochondrial genomes of the three populations of L. chinensis were 16028, 15580 and 15580 bp in size. They contained 13 protein-coding genes (PCGs), 2 ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs) and a non-coding A+T-rich region; these occurred in the same order and orientation observed in previously sequenced mitochondrial genomes of other lepidopterans. The A+T-rich regions of the three populations, located between srRNA and tRNA Met, contained some conserved structural characteristics of lepidopterans, such as the motif 'ATAGAA' followed by an 11-bp poly-T stretch and a 13-bp poly-A stretch at the 3′ end. The phylogenies of 29 mitogenomes of Papilionidae constructed using ML and BI methods showed identical topology and were consistent with morphological and molecular taxonomy. The Ningshan population of L. chinensis does not represent a separate species.